A Dual Spectroscopic Probe Based on Benzothiazole for Detection of Hydrazine. Issue 29 (11th August 2021) - Zhang, Shiqing; Li, Lingling; Zhu, Jinbiao; Mu, Xinyue; Yan, Liqiang; Wu, Xiongzhi
Abstract: Hydrazine is widely used in fuels, fuel cell reactors and the synthesis of polymer, drug and pesticide intermediates. However, it can be contained in food and drinking water and enter organisms through the food chains because of its good water solubility, causing serious health problems. Therefore, there is an urgent need to develop new analytical reagents to detect hydrazine with high selectivity and sensitivity. In this paper, a spectroscopic probe (probe 1 ) for hydrazine hydrate based on the addition‐cyclization mechanism with high selectivity and sensitivity was developed. This probe can simultaneously detect hydrazine by UV‐visible and fluorescence spectra, and the corresponding detection limits are 51.7 μM and 6.7 nM, respectively. Importantly, the spectroscopic probe was successfully applied to hydrazine detection in water samples and living cells. The test strips based on the probe was also prepared for the point‐of‐care testing of hydrazine in the actual water samples. Abstract : A dual spectroscopic benzothiazole‐based probe based on the addition cyclization reaction mechanism has been developed, which can effectively detect hydrazine (N2 H4 ) in water samples and living cells by UV‐visible and fluorescence spectra, and can be prepared as the convenient test paper to detect hydrazine hydrate. This probe provides a reliable testing method for N2 H4 .